UMP Foundation donates Covid-19 Aid Kit for Ramadan - UMP, PNC (2020)
Concerned for the current situation of Movement Control Order (MCO) and the forthcoming of Ramadan, UMP Foundation distributed assistance to the frontliners and the staff in need on 17 April 2020.